Hubungan Motivasi dengan Kepatuhan Perawat dalam Menerapkan Pencegahan Risiko Jatuh di Rumah Sakit Islam Sultan Agung Banjarbaru - Nayla Azkia; Muh Abdurrouf; Retno Issroviatiningrum (Quantum Wellness : Jurnal Ilmu Kesehatan, 2025)
Patient safety is a crucial aspect of hospital service quality, with one of the main indicators being the prevention of fall risks. Fall risks among patients often lead to serious injuries and impact the quality of care, making preventive measures essential. Nurses play a central role in implementing these preventive actions. However, the level of nurse compliance in following preventive procedures is often influenced by work motivation. This study aims to analyze the relationship between work motivation and nurse compliance in implementing fall risk prevention at the Sultan Agung Islamic Hospital in Banjarbaru. This quantitative study used a cross-sectional design, involving 97 inpatient nurses as respondents. The instruments used in this study included a 20-item Likert scale questionnaire to measure motivation and an observation sheet with 10 items to assess nurse compliance in applying fall risk prevention procedures. The data collected were analyzed using the Somers’ D test to determine the strength and direction of the relationship between the two variables. The results showed that the majority of nurses had high motivation (92.8%) and high compliance (90.7%) in implementing the prevention procedures. The Somers’ D test revealed a significant relationship between work motivation and nurse compliance in fall risk prevention (p = 0.003; d = 0.866), indicating that higher work motivation leads to higher compliance. The conclusion of this study is that work motivation is closely related to nurse compliance in fall risk prevention. Therefore, enhancing work motivation should be an important strategy for hospital management in developing a better patient safety culture.